Natural enemies of the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) in Ghana - Koffi, D.; Kyerematen, R.; Eziah, V.Y.; Agboka, K.; Adom, M.; Goergen, Georg E.; Meagher Jr, R.L. (Florida Entomological Society, 2020)
The fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), is an invasive insect pest attacking maize in Ghana and sub-Saharan Africa countries. Biological control will need to be an important management strategy, and a first step was to identify potential natural enemies. Sampling was conducted in different localities of the 10 regions of Ghana from May to Nov 2017. A total of 1,062 larvae were collected from 106 maize farms, and the presence of natural enemies was recorded in 18 (17.0%) farms. Among natural enemies recorded, 7 species were parasitoids: Chelonus bifoveolatus Szpligeti, Coccygidium luteum (Brull), Cotesia icipe Fernandez, Meteoridea testacea (Granger), and Bracon sp. (all Hymenoptera: Braconidae), Anatrichus erinaceus Loew (Diptera: Chloropidae), and an undetermined tachinid fly (Diptera: Tachinidae). The parasitism rate was 3.58%. Three predator species were collected: Pheidole megacephala (F.) (Hymenoptera: Formicidae), Haematochares obscuripennis Stål, and Peprius nodulipes (Signoret) (both Heteroptera: Reduviidae). The 2 most abundant parasitoids were C. bifoveolatus and C. luteum with a relative abundance of 29.0% and 23.7%, respectively, and a parasitism rate of 1.04% and 0.85%, respectively. However, C. bifoveolatus was the most dispersed parasitoid, found in 6.6% of the inspected sites within all the agroecological zones of Ghana. This species is a good candidate as a biological control agent for fall armyworm in Africa. The predator that was most abundant (46.0%) and dispersed (3.8% of the farms) was P. megacephala.